Comparison of serial blood lactate level between dengue shock syndrome and dengue hemorrhagic fever (evaluation of prognostic value) - M. Tatang Puspanjono; Abdul Latief; Alan R. Tumbelaka; Sudigdo Sastroasmoro; Hartono Gunardi (Paediatrica Indonesiana, 2007)
Background Dengue shock syndrome (DSS) mortality is still high.Monitoring of blood lactate level is important to evaluate shock.Objectives The study were to review the difference between bloodlactate level of DSS and that of dengue hemorrhagic fever (DHF),to correlate blood lactate level with hypoxia state as shock riskfactors (PaO 2 , oxygen saturation, and anion gap) and to determinethe cut-off point of blood lactate level to predict shock.Methods The study was carried out at the Department of ChildHealth, Medical School, University of Indonesia, CiptoMangunkusumo Hospital, Jakarta, from January until July 2006.Three mL venous blood specimen was collected from all subjectsfor peripheral blood, blood gasses, serology, and blood lactateexaminations. This study consisted of a retrospective cohort anda cross sectional method. Data were analyzed with Chi-squaretest. Continous data tested using Mann-Whitney method. Toknow the correlation between blood lactate level and shock riskfactors we use logistic regression test.Results In DSS group, 73% shows hyperlactatemia (lactate =2mmol/L). Conversion of lactate means between two groups issignificantly different from day one to day two and three. Therewas a negative correlation between lactate level and pO 2 andoxygen saturation. Oxygen saturation is the only value that hasclinical correlation. Regressions analysis can be applied using Y= 7.05–0.05 X equation. The cut-off point of lactate level asmarker for shock by using ROC curve is 32.015 mmol/L with 70%sensitivity and 83.3% specificity.Conclusions Hyperlactatemia in DSS can be considered as a signfor unappropriate treatment of shock. Blood lactate level can beused as a biochemical marker for tissue hypoxia, to assess severityof the disease, as monitoring of treatment, and has prognosticvalue of DHF cases.